Improving Problem-Solving Student Ability: Integrating Google Earth with SETS Model Learning for Effective Solutions - Khoirunnisaa' Khoirunnisaa'; Muhammad Rizieq Fahmi (Abjadia, 2023)
The ability to solve problems is one of the fundamental skills in learning geography in this era. The SETS (Science, Environment, Technology, Society) learning model integrated with Google Earth makes it easier for students to use science and technological literacy as a tool to determine actions in solving problems. This study aimed to determine the effect of the SETS learning model integrated with Google Earth on the problem-solving ability of high school students. The method used is a quasi-experiment with a pretest-posttest control group research design. The research subjects consisted of 70 students (35 students in the experimental class and 35 students in the control class). The results showed that the increasement in problem-solving skills by students in the experimental class was higher than the control class. This research proves that the SETS learning model assisted by Google Earth has a positive effect on students' problem-solving abilities. However, SETS learning model integrated with Google Earth still needs to be further understood by students. So, in its implementation, it is necessary to give detailed initial instructions to students about the stages of learning and using Google Earth.